RESISTÊNCIA À PENETRAÇÃO EM NEOSOLO QUARTZARÊNICO DEGRADADO FISICAMENTE. - BARCELOS, Rian Pereira Barcelos; GUIMARÃES JÚNNYOR, Wellingthon da Silva; ASSUNÇÃO, José Jorge Lopes de Assunção; RODRIGUES, Jose Augusto Dos Santos Rodrigues; NASCIMENTO, Ana Carolina Vidal do Nascimento (ANAIS DO ENIC, 2025)
-